COVID‐19 in lung transplant recipients - Myers, Catherine N. (Transpl Infect Dis, 2020)
Solid organ transplant recipients are considered at high risk for COVID‐19 infection due to chronic immune suppression; little data currently exists on the manifestations and outcomes of COVID‐19 infection in lung transplant recipients. Here we report 8 cases of COVID‐19 identified in patients with a history of lung transplant. We describe the clinical course of disease as well as preexisting characteristics of these patients.